4-Methylcatechol, a Flavonoid Metabolite with Potent Antiplatelet Effects - Applova, Lenka; Karlickova, Jana; Warncke, Paul; Macakova, Katerina; Hrubsa, Marcel; Machaek, Miloslav; Tvrdy, Vaclav; Fischer, Dagmar; Mladenka, Premysl (Molecular Nutrition & Food Research, 2019)
Scope: Intake of flavonoids from the diet can be substantial, and epidemiological studies suggest that these compounds can decrease the incidence of cardiovascular diseases by involvement with increased platelet aggregation. Although parent flavonoids possess antiplatelet effects, the clinical importance is disputable due to their very low bioavailability. Most of them are metabolized by human colon bacteria to smaller phenolic compounds, which reach higher plasma concentrations than the parent flavonoids. In this study, a series of 29 known flavonoid metabolites is tested for antiplatelet potential. Methods and results: Four compounds appear to have a biologically relevant antiplatelet effect using whole human blood. 4-Methylcatechol (4-MC) is clearly the most efficient being about 10× times more active than clinically used acetylsalicylic acid. This ex vivo effect is also confirmed using a potentially novel in-vivo-like ex ovo hen's egg model of thrombosis, where 4-MC significantly increases the survival of the eggs. The mechanism of action is studied and it seems that it is mainly based on the influence on intracellular calcium signaling. Conclusion: This study shows that some flavonoid metabolites formed by human microflora have a strong antiplatelet effect. This information can help to explain the antiplatelet potential of orally given flavonoids.
CRIS-Team Scopus Importer:2020-10-13
Keywords: 4-methylcatechol; aggregation; flavonoids; metabolites; platelets; pyrogallol